PSYCHOLOGY IN SPORT: BRIDGING THEORY AND PRACTICE - Kolesyanova, Asya; Kolesyanov, Ildar (Журнал Педагогики и психологии в современном образовании, 2023)
Psychology's profound influence on sports performance and athlete well-being underscores its pivotal role in sports contexts. This article aims to explore the dynamic interplay between psychological theory and practical application within the realm of sports. The objective is to investigate how established psychological theories are translated into actionable strategies to enhance athlete training, motivation, and overall performance. To achieve this aim, a comprehensive review of key psychological theories, such as self-determination theory, cognitive appraisal theory, and the zone of proximal development, is conducted. The review involves analyzing the foundational principles of these theories and their implications for athlete development. The results of this analysis highlight the multifaceted ways in which psychology influences athlete training and performance. From fostering intrinsic motivation to optimizing stress management, psychological theories offer valuable insights that can be integrated into training programs. The synthesis of theory and practice yields enhanced athlete outcomes, as demonstrated by the case studies. This article underscores the symbiotic relationship between psychological theory and its application in the sporting arena. By bridging the gap between theoretical insights and practical strategies, sports psychology contributes to the holistic development of athletes. This exploration emphasizes the significance of integrating psychological principles into athlete training and underscores the continued importance of research in advancing the field of psychology in sport.